Associations between Fat Mass and Fat Free Mass with Physical Fitness in Adolescent Girls: A 3-Year Longitudinal Study - Mario Kasović; Ana Oreški; Tomáš Vespalec; Marta Gimunová; Lovro Štefan (Biology, 2022)
The main purpose of the study was to examine the longitudinal associations between fat mass and fat free mass with health-related physical fitness. Two-hundred and forty 15-year old adolescent girls were measured at the baseline and after a period of 3 years (17 years). Health-related physical fitness included the following tests: (1) explosive power of the lower extremities (standing broad jump); (2) muscle endurance of the trunk (sit-ups in 60 s); (3) flexibility (sit-and-reach test); (4) muscle endurance of the lower extremities (squats in 60 s); (5) aerobic endurance (the 800 m run test); and (6) speed endurance (the 400 m running test). Fat mass and fat free mass were assessed using the bioelectrical impedance method. Longitudinal associations were analyzed with linear mixed model estimates. After adjusting for body mass index, fat mass was negatively associated with standing broad jump (β = −1.13, p < 0.001), sit-ups in 60 s (β = −0.27, p < 0.001), and squats in 60 s (β = −0.27, p < 0001), while positive associations with the 800 m running test (β = 0.02, p < 0.001) and the 400 m running test (β = 0.02, p < 0.001) were observed. On the other hand, fat free mass was positively associated with standing broad jump (β = 1.14, p < 0.001), sit-ups in 60 s (β = 0.28, p < 0.001), and squats in 60 s (β = 0.28, p < 0001), while the 800 m running test (β = −0.02, p < 0.001) and the 400 m running test (β = −0.02, p < 0.001) exhibited negative associations. This study shows that fat mass and fat free mass components are longitudinally, but oppositely associated with health-related physical fitness in adolescent girls.